The impact of cycling hypoxia on the phenotype of HPV-positive cervical cancer cells - Heber, Nora; Kuhn, Bianca; Strobel, Tobias; Lohrey, Claudia; Krijgsveld, Jeroen; Hoppe-Seyler, Karin; Hoppe-Seyler, Felix (Journal of medical virology, 2023)
Cycling hypoxia (cycH) is a prevalent form of tumor hypoxia that is characterized by exposure of tumor cells to recurrent phases of hypoxia and reoxygenation. CycH has been associated with a particularly aggressive cellular phenotype of tumor cells and increased therapy resistance. By performing comparative analyses under normoxia, physoxia, chronic hypoxia, and cycH, we here uncover distinct effects of cycH on the phenotype of human papillomavirus (HPV)-positive cervical cancer cells. We show that—other than under chronic hypoxia—viral E6/E7 oncogene expression is largely maintained under cycH as is the E6/E7-dependent regulation of p53 and retinoblastoma protein. Further, cycH enables HPV-positive cancer cells to evade prosenescent chemotherapy, similar to chronic hypoxia. Moreover, cells under cycH exhibit a particularly pronounced resistance to the proapoptotic effects of Cisplatin. Quantitative proteome analyses reveal that cycH induces a unique proteomic signature in cervical cancer cells, which includes a significant downregulation of luminal lysosomal proteins. These encompass the potentially proapoptotic cathepsins B and cathepsin L, which, however, appear not to affect the response to Cisplatin under any of the O2 conditions tested. Rather, we show that the proapoptotic Caspase 8/BH3-interacting domain death agonist (BID) cascade plays a pivotal role for the efficiency of Cisplatin-induced apoptosis in HPV-positive cancer cells under all investigated O2 conditions. In addition, we provide evidence that BID activation by Cisplatin is impaired under cycH, which could contribute to the high resistance to the proapoptotic effects of Cisplatin. Collectively, this study provides the first insights into the profound phenotypic alterations induced by cycH in HPV-positive cancer cells, with implications for their therapeutic susceptibility.